Cyberchondria Amidst COVID-19 Pandemic: Challenges and Management Strategies - Varma, Rahul; Das, Sreeja; Singh, Tushar (Frontiers in Psychiatry, 2021)
The Coronavirus disease 2019, first found in Wuhan, China in December 2019, has posed an inexplicable threat to the global community. After its inception, the virus proliferated rapidly which led to the cause of million deaths, and having a detrimental effect on physical health, social lives, economy uncertainty and mental health of people. According to the reports of the World Health Organization (WHO), there are 37.8 million confirmed cases of COVID-19 and 1.08 million deaths due to COVID-19. Indisputably, the present pandemic has contributed to the extensive psychological and environmental distress including anxiety, depression, post-traumatic stress disorder, domestic violence and unemployment. Due to the pandemic, the educational organizations and outdoor activities are closed, thus burdening the mental health of the younger populations. Children are more glued to the internet to study, play online games, shop, to watch movies, and search health related information. Despite the advantages of using the internet, it has some severe consequences too. Some people are repeatedly searching physical and mental wellbeing related information without verifying the credible sources, which in turn causing distress and anxiety. In such situations, individuals may end up contributing to an illness known as Cyberchondria. This article highlights the problematic use of internet for health related searches and have outlined the management of such illness. Two strategies suggested are- the reduction of the repeatedly online searches of health information and secondly, to manage the anxiety-augmenting thoughts which are triggered due to the maladaptive thoughts caused by the abstruse information.